The study of masculinities. (2014) - ,
Abstract : Purpose – The purpose of this paper is to review the development of the field of knowledge about masculinities, and particularly to show the need for post‐colonial perspectives.Design/methodology/approach – Reading major texts in the field and analysing their conclusions, inclusions, and exclusions.Findings – Study of masculinities is necessary to gain an adequate understanding of the whole field of gender relations. This field is now global, but the consequences of a global field of knowledge are not sufficiently recognized because of the continuing hegemony of the global north in theory, methodology, and academic networks. The coloniality of gender is outlined. Significant contributions from the global south are identified and the issues involved in decolonizing the field of masculinity studies are analysed.Research limitations/implications – Mainly Anglophone texts discussed.Practical implications – Redesign of curricula for teaching in this area; redeployment of resources in academic publishing and other knowledge production projects.Social implications – Knowledge in this area is relevant to HIV prevention, poverty reduction, economic development, prevention of violence, international conflict, and educational attainment.Originality/value – To stimulate rethinking among scholars in the field of masculinity and gender studies, and through them among those dealing with the practical issues mentioned.